Student satisfaction towards food quality in dining hall at Uitm Terengganu campus Dungun / Norsyafiqah Md Amin & Rohidayu Razali - Md Amin, Norsyafiqah; Razali, Rohidayu (Faculty of Hotel and Tourism, 2018)
Foodservice in school, college and university is the largest food-service business in the world. Students will choose to have meals in the cafeteria, because they might lack the time and it is convenient. However, canteen or cafeteria in the university is difficult to satisfy students for example in terms of food preparation and does not meet what they want especially in terms of the quality of the food. It will determine their satisfaction level on the cafeteria in UiTM Terengganu branch campus Dungun. This research is about to study student satisfaction towards food quality in dining hall in UiTM Terengganu. The quality of a food will affect a person whether positive or negative influence on the atmosphere in cafeteria or canteen. This is because most students will find food in the place. They expect the cafeteria to meet their tastes and so on. Customer’s satisfaction in the aspect of business is important when providing service because they are the main contributor to the business success and getting more profit. So, the students filled out the survey which focused on the food quality and asked students how they felt about the food, convenience and others. Last, this study also evaluated the survey and explored the overall satisfaction of the students in the cafeteria, the analysis showed areas where satisfaction was being net and also where improvement could be made.